Cytotoxic and apoptotic effects of constituents from Millettia pachycarpa Benth - Ye, Haoyu (2013)
The aim of this study is to investigate the cytotoxic and apoptotic effects of constituents from the seeds of Millettia pachycarpa Benth. Fourteen compounds (1–14) including one novel chalcone (10) were isolated as active principles from Chinese herbal medicine M. pachycarpa Benth. Their structures were identified by using spectroscopic methods. All isolates were then evaluated for their cytotoxic effects against several cancer cell lines (HepG2, C26, LL2 and B16) with cisplatin as a positive control. And their apoptosis-inducing effects were tested against HeLa-C3 cells with taxol as a positive control. Both studies showed that compounds 1, 2, 7 and 10 demonstrated significant cytotoxic and apoptotic effects against cancer cells. Moreover, in the apoptosis assay the novel chalcone (10) showed strong apoptosis inducing effects at a concentration of 2 μM within 36 h. It was found to be the most potent apoptotic inducer of the compounds isolated from M. pachycarpa Benth.